Optimalisasi Metode Demonstrasi Berbantuan Media Nyata dalam Pengajaran IPA pada Siswa Sekolah Dasar - Agustina (PT. Media Edukasi Borneo, 2021)
This study aimed to determine the application of demonstration methods assisted by real media in an effort to increase activeness and learning outcomes in science learning. Classroom action research was employed with 2 cycles. The study participants were students of grade V in one of the state elementary schools in Bengkayang Regency, West Kalimantan, totaling 11 girls and 13 boys. Data collection used observation and tests. Observation was implemented to identify learning activeness and tests were used to measure students' ability to master the learning materials. The results of the observation of learning activeness of students in cycle I averaged 69.06%, demonstration activities on average 69.81% with classical completeness of 4.16% increased in cycle II to 83.93% of demonstration activities 91.59% of classical completeness 75 %. Actions taken in which the students were asked to perform demonstrations in front of the class, demonstrate, and to summarize the results of group demonstrations. While the learning outcomes of the first cycle 66.67% increased to 87.50% in the second cycle. The results of this study implied that the application of demonstration methods assisted by real media increased student activity and learning outcomes. ABSTRAK Penelitian ini bertujuan untuk mengetahui penerapan metode demonstrasi berbantuan media nyata dalam upaya meningkatkan keaktifan dan hasil belajar dalam pembelajaran IPA. Penelitian tindakan kelas digunakan dengan 2 siklus. Partisipan penelitian adalah siswa kelas V di salah satu sekolah dasar negeri di Kabupaten Bengkayang, Kalimantan Barat yang berjumlah 11 perempuan dan 13 laki-laki. Pengumpulan data menggunakan observasi dan tes. Observasi digunakan untuk mengidentifikasi keaktifan belajar dan tes digunakan untuk mengukur kemampuan siswa dalam menguasai materi pelajaran. Hasil observasi keaktifan belajar siswa siklus I rata-rata 69,06%, kegiatan demonstrasi rata-rata 69,81% dengan ketuntasan klasikal 4,16% meningkat pada siklus II menjadi 83,93% kegiatan demonstrasi 91,59% ketuntasan klasikal 75%. Tindakan yang dilakukan yaitu siswa diminta melakukan demonstrasi di depan kelas, serta diminta membuat kesimpulan hasil demonstrasi kelompok. Sedangkan hasil belajar siklus I 66,67% meningkat menjadi 87,50% pada siklus II. Dari hasil penelitian ini, dapat disimpulkan bahwa penerapan metode demonstrasi berbantuan media nyata dapat meningkatkan keaktifan dan hasil belajar siswa. KATA KUNCI: pendidikan dasar, IPA, demonstrasi, keaktifan, hasil belajar